Trend analysis of catching fish Decapterus sp. in the Muncar Coastal Fisheries Port, Banyuwangi, Indonesia - Devi Purwinda; Hany Handajani; Anis Zubaidah (IJOTA (Indonesian Journal of Tropical Aquatic), 2020)
Small pelagic fish resources in the Java Sea, especially Banyuwangi, are dominated by catches of Decapterus sp, which are mostly landed at the UPT of the Coastal Fisheries Port Muncar. This study aimed to provide information on CPUE trends (Catch Per Unit Effort) and the seasonality of flying fish in the Coastal Fisheries Port Muncar as an effort to encourage effective and sustainable in using of fishery resources. The method used in this study was a survey. The research data was obtained through secondary data including time series of the production of catches of flying fish, and trip data of purse seine, payang and bagan from 2015 to 2019 collected by Coastal Fisheries Port Muncar. The analysis used the CPUE analysis by comparing catches to capture attempts. The results showed, from 2015 to 2019, the highest CPUE of flying fish occurred in 2019, amounting to 13 365.5 kg/trip, while the lowest CPUE occurred in 2016 amounted to 1 050.6 kg/trip. The trend of CPUE flying fish from 2015 to 2019 experienced a fluctuating increase with an average of 7 327.5 kg/trip. A good season for flying fishing occurs from May to December, and shares a peak in December, while famine occurs in January.